Culture and Language: A Research on the Situation and Conditions of Education at Ban Tha Map Rao School, Krabi, Thailand - Sholehudin, Sholehudin; Burhendi, Felicianda Adrin (CV. Ulil Albab Corp, 2024)
Education is a key to determining the direction of the future. Because with quality education, dreams can be achieved. Therefore, education is a major concern in preparing an intelligent and qualified generation. The aim of providing service to the Ban Tha Map Rao school is to find out about the social, cultural and linguistic conditions at the school. The service method that I use is the classroom Image Visualization method to find out what the purpose of service is. And the results of the service carried out are that Ban Tha Map Rao School has a culture of high discipline, order, and is able to respect differences in beliefs so as to create a quality school ecosystem.